Paramagnetic Levitational Assembly of Hydrogels. (10th December 2012) - Tasoglu, Savas; Kavaz, Doga; Gurkan, Umut Atakan; Guven, Sinan; Chen, Pu; Zheng, Reila; Demirci, Utkan
<x xml:space="preserve">Abstract</x> We have presented, for the first time, hydrogels that can be directed and assembled into 3D constructs by exploiting their magnetic properties without using magnetic particles. We have performed experimental and theoretical analyses to describe hydrogel motion in a fluidic environment under a magnetic field. <boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>